(untitled) (Journal of Philosophy Culture and Political Science, 2023)
In this article, considering the value orientations of Kazakhs in Turkey from the point of view of their own modernization, it is tried to determine the importance of mutual communication with compatriots. The study of the peculiarities of the value-meaning world of the modern Kazakh diaspora and its cultural analysis were carried out. A small ethnic community usually forms its culture in accordance with the official spatial laws of historical entities that dominate the environment in which they live and play a culturally dominant role. The laws arising from these relations determine the special character of the way of life of all diaspora communities, and the Kazakh diaspora is not excluded from these mutual relations. The study of the value system of the Kazakh diaspora abroad today is a requirement of modern scientific and innovative development. Among them, the study of socio-cultural cooperation is important from a worldview point of view. In the study, using various scientific paradigms of the study of the value system of the ethnic group, the cultural climate and values of the ethnic community abroad were theoretically and practically analyzed. The life, cultural appearance, features of the world of values of foreign Kazakhs were studied, and the theoretical and methodological aspects of the study of the axiological features of the diaspora ethnic self-consciousness were determined. The social orientations of foreign ethnic groups in the socio-professional structure in other national environments, the degree of prestige of the types of activities, the established social, economic and cultural role were studied. Its advantages in industrial and household industries have been identified. In order to determine the political, social, legal, and cultural advantages of foreign Kazakhs, the degree of adherence to the way of life, traditions and customs was monitored. Key words: сulture, value, brend, factor, cultural research